Special Issue on Light Beams in Liquid Crystals - Assanto, Gaetano; Smyth, Noel F. (Applied sciences, 2022)
Introduction The study of propagating light beams in liquid crystals, i.e., soft-matter encompassing optical birefringence, nonlocality, anisotropy and all-optical, as well as electro-optic, magneto-optic and thermo-optic responses, has been the subject of extensive experimental and theoretical investigations. Owing to such wide-ranging importance, comprehensive papers are available in the literature on the optics and photonics of liquid crystals with reference to solitary waves, random lasing, topological and spin–orbit interactions of light, to cite just a few [2,3,4,5]. A hybrid system consisting of gold nanoparticles immobilized on a glass substrate and layered with photo-aligned liquid crystals is developed, with the photo-aligning material providing molecular reorientation and tunability.